A project manager's book of tools and techniques a companion to the PMBOK Guide (John Wiley & Sons. Inc., 2018)
Designed specifically to assist both new and experienced project managers in handling all aspects of a project, this title explins the "how" when it comes to project management theory. Concrete examples of tools for project managers will fill the gap in this PM knowledge area and provide necessary guidance for both practicing project managers and students